Low voltage low power WiMAX VCO design - Ong, Chin Leong. (2010)
A 2.2 GHz, 0.57 V voltage controlled oscillator is designed and simulated using Cadence SpectreRF 0.18-um CMOS process. The topology of the circuit makes use of two parallel LC resonators with four negative differential resistance transistors. At supply voltage of 0.57 V, the oscillator draws a current of 2.4 mA, consuming 1.386 mW of power. The phase noise of the oscillator is less than -116.2 dBc/Hz at 1MHz offset frequency. Tuning range is from 2.101 to 2.255 GHz, with corresponding tuning voltage from 0.7 to 1.5 V.